Indonesian Health Workers during COVID-19 Pandemic - Ari Fahrial Syam (The Indonesian Journal of Community and Occupational Medicine, 2021)
Burnout in health workers causes physical and emotional fatigue; it is a condition of a long-term affective state and is an outcome of cumulative and chronic exposure to stress, particularly work stress. Burnout was especially evident in hospitals with limited availability of medical staff. Mental burdens are higher because they face more patients infected by the coronavirus, followed by the trauma of witnessing deaths among patients. These conditions may weaken the immune system, increasing vulnerability to COVID-19 and higher risk of severe symptoms that can cause death. When talking out of context of the pandemic, burnout can also be associated with various other diseases, including IBS.4 Burnout was associated with a 2.41-fold elevated prevalence of IBS after adjusting for potential confounding variables, including job strain.